Synthesis, odour characteristics and antibacterial activities of the stereoisomeric forms of whisky lactone and its thiono analogues. (4th September 2016) - Shimotori, Yasutaka; Hoshi, Masayuki; Okabe, Hayato; Miyakoshi, Tetsuo; Kanamoto, Taisei; Nakashima, Hideki
Abstract: Four stereoisomers of whisky lactone were selectively synthesized in over 99% enantiomeric excess using an amino acid derivative as a resolving agent. Cbz‐L‐proline was the most effective resolving agent, and both trans ‐ and cis ‐stereoisomers were comparatively easily separated. Odour characteristics of whisky thionolactone were different among four stereomeric isomers, and only (3 S, 4 R )‐whisky thionolactone had mushroom and cis ‐jasmone like note. Among all isomers, only (3 R, 4 S )‐whisky lactone showed antibacterial activities against Staphylococcus aureus . Whisky thionolactone had higher activities than whisky lactone, and (3 R, 4 S )‐whisky thionolactone showed the strongest activities of all tested samples. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Four stereoisomers of whisky lactone were selectively synthesized in over 99% enantiomeric excess using diastereomeric resolution. Odour characteristics and antibacterial properties were investigated for four stereoisomers of whisky lactone and its thiono analogues. All stereoisomers showed different odour characteristics, and only (3 R, 4 S )‐whisky thionolactone had mushroom and cis‐jasmone like note. Whisky thionolactone had higher activities than whisky lactone against Staphylococcus aureus, and (3 R, 4 S )‐whisky thionolactone showed the strongest activities.